Experimentos probabilísticos: noções de probabilidade no ensino fundamental II - Biajoti, Emerson Donizeti (2013)
This work has as its main goal to show the results of an instructive and pedagogical research which uses games with coins and dice, whose solutions and appropriate teacher´s mediation, allow the student to make the construction about the initial concepts of Probability. This research, through the engineering instructive method, took place in four different 7th grade classrooms in a public school, in the countryside of the state of São Paulo. The results show that the use of such a teaching proposal may improve learning, make the classes more interesting and help the students to take real part in them. The learners become the chief builders in the evolution of their own knowledge. The study about Probability problems was part, for many years, of High School only. Yet this subject can be taught to younger students as well, what has been widely recognized by the PCNs, published by MEC. In order to make these learnings related to Probability a reality we must change, which is just something imposed in our text books, in real experiences. It is suggested to toss a coin several times, discuss and reflect about this procedure, helping the students observe and make presumptions about how and why the chance of being winners in a heads or tails game is of 50%. According to the PCNs (BRAZIL, 1998), the notions about Probability must be explored through experiences and simulations to calculate the Probabilities themselves and check expected Ones.